4/x+2 - 1/x+3 = 4/2x+1 solved it by factorization method.
Answers
Answered by
1
This is the step wise explanation of the above question....
Attachments:
![](https://hi-static.z-dn.net/files/d61/98966b4c3b5e31f459e9f158e1497c75.jpg)
Answered by
0
4/x+2 - 1/x+3 = 4/2x+1
4(x+3) - 1(x+2)/(x+2)(x+3) = 4/2x+1
4x+12 - x - 2/x^2+3x+2x+6 = 4/2x+1
3x+10/x^2+5x+6 = 4/2x+1
3x+10(2x+1)=4(x^2+5x+6)
3x+20x+10=4x^2+20x+24
23x+10=4x^2+20x+24
23x-20x=4x^2+24-10
3x=4x^2+14
4x^2-3x+14=0
FACTORISE AFTER THIS
MARK AS BRAINLIEST
Similar questions
Math,
6 months ago
History,
6 months ago
Math,
6 months ago
Business Studies,
1 year ago
CBSE BOARD XII,
1 year ago
Math,
1 year ago